2019
DOI: 10.1515/hsz-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of astrocytes to metabolic dysfunction in the Alzheimer’s disease brain

Abstract: Historically considered as accessory cells to neurons, there is an increasing interest in the role of astrocytes in normal and pathological conditions. Astrocytes are involved in neurotransmitter recycling, antioxidant supply, ion buffering and neuroinflammation, i.e. a lot of the same pathways that go astray in Alzheimer’s disease (AD). AD remains the leading cause of dementia in the elderly, one for which there is still no cure. Efforts in AD drug development have largely focused on treating neuronal patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 148 publications
0
17
0
Order By: Relevance
“…As pyruvate flux into the mitochondria is regulated by the mitochondrial pyruvate carrier (MPC), the authors suggest that this is an essential regulatory control point between basal respiration and gluconeogenesis in astrocytes. Therefore, this data suggests that modulation of pathways such as gluconeogenesis may have therapeutic potential in neurological diseases where there is a significant metabolic component such as Alzheimer's disease (AD, see Zulfiqar et al for a recent review see [21]). For example, astrocytes expressing the E4 allele of Apo-lipoprotein E (APOE), a genetic risk factor for AD, were shown to have increased glucose flux via the pentose phosphate pathway (PPP).…”
Section: Astrocyte Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…As pyruvate flux into the mitochondria is regulated by the mitochondrial pyruvate carrier (MPC), the authors suggest that this is an essential regulatory control point between basal respiration and gluconeogenesis in astrocytes. Therefore, this data suggests that modulation of pathways such as gluconeogenesis may have therapeutic potential in neurological diseases where there is a significant metabolic component such as Alzheimer's disease (AD, see Zulfiqar et al for a recent review see [21]). For example, astrocytes expressing the E4 allele of Apo-lipoprotein E (APOE), a genetic risk factor for AD, were shown to have increased glucose flux via the pentose phosphate pathway (PPP).…”
Section: Astrocyte Metabolismmentioning
confidence: 99%
“…However, in iPSCs, GW0742 did not protect against pro-inflammatory activation and in the mouse model, astrogliosis was unaffected, indicating that increasing FAO does not reverse the metabolic deficit fully. This may be because astrocyte metabolic adaptation to fatty acid dependent respiration in times of glucose hypometabolism (as observed in AD for example [21] comes at a cost. Recent work in primary astrocytes has suggested that glucose starvation leads to activation of 5' adenosine monophosphate-activated protein kinase.…”
Section: Is Astrocyte Lipid Pathway Manipulation Beneficial In Neurological Disorders?mentioning
confidence: 99%
“…In addition to the historical description of the pathology that include β amyloid plaques and hyperphosphorylated tau in the brain, it is characterized by clear mitochondrial and metabolic impairments (Butterfield and Halliwell, 2019). Hence, AD can be considered as a metabolic disease with impairment in mitochondrial bioenergetics, as well as glucose brain import and metabolism (Zulfiqar et al, 2019).…”
Section: Brain Energy Metabolic Dysfunctions In Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore, the observations of Harris et al (2019) suggest that lactate production may be required for memory acquisition but not retrieval. Hence, boosting the neuroprotective properties of astrocytes (by boosting lactate production of astrocytes) has potential applications in delaying the onset and progression of AD, as originally proposed by Demetrius et al (2015) and summarized in a review by Zulfiqar et al (2019). Furthermore, glucose hypometabolism is typically observed in AD.…”
Section: Lactate Is Indispensable In Neurodegenerative Diseasesmentioning
confidence: 99%